Partial chaos suppression in a fractional order macroeconomic model - David, S. A.; Machado, J. A. T.; Quintino, D. D.; Balthazar, J. M. [UNESP] (Elsevier B.V., 2016)
This work investigates the possibility of suppressing chaos in a fractional-nonlinear macroeconomic dynamic model. The system generalizes a model recently reported in the literature in which chaos is strongly present. This description involves the inclusion of the public sector deficit and its coupling with other variables. The system is simulated for integer and non-integer orders that produce a complex dynamics. The time histories and the phase diagrams are presented. The main contribution of this work refers to the adoption of the largest Lyapunov exponent (LLE) criteria based on Wolf's algorithm. This approach improves the response of the system, suppressing, at least partially, the strong presence of chaos reported in previous studies. (C) 2015 International Association for Mathematics and Computers in Simulation (IMACS). Published by Elsevier B.V. All rights reserved.
Keywords: Macroeconomic model; Fractional calculus; Numerical simulations; Nonlinear systems; Chaos